From humanism to neohumanism, posthumanism and transhumanism: pedagogical reading - Ольга Сухомлинська (Філософія освіти)
The article is dedicated to highlighting the concepts of humanism, neohumanism, posthumanism, transhumanism, their reading through the prism of pedagogical science and practice. The text is based on analysis of Ukrainian, French, and Polish sources, as well as own considerations. It has been found that the classical interpretation of humanism during the last decades has been subject to revision by various researchers due to the growing contradictions between the social, economic, and spiritual needs of society and the consideration of humanism with its anthropocentric attitude towards man as the measure of all things. It was found that they led to an expanded and modified understanding of it, which was called neohumanism (new humanism). The article describes the researchers’ interpretation of neohumanism, which is based on moral and ethical ideas and ideals that relate to philosophical, ecological, pedagogical and other aspects of human life. It was noted that because of the sharp growth of new technologies, two concepts critical to humanism/ neohumanism emerged – posthumanism and transhumanism. The text reveals the concept of posthumanism, which, according to the researchers, considers man in unity, merging with machines, technological devices, that is, human and non-human. The main characteristics of post-humanist trends are provided, which testify to the gradual disappearance of man as an active and self-sufficient effective person. It is noted that, accordingly, transhumanism, as a radicalized branch of posthumanism, is focused on the use of technologies with the aim of creating a physically and mentally perfect person (Homo Perfectus), when the difference between man and machine is erased. It is shown how these processes affect the modern education system, which absorbs new technologies at an accelerated pace, replacing its traditional tools for teaching reading, writing, arithmetic, aimed at the formation of «long» memory, with technological devices. The article also raises the issue of neo-humanism, which is biocentric in nature, and in the pedagogical aspect manifests itself as a humane attitude towards nature, living beings, primarily animals. Such a trend becomes especially relevant in the context of ecocide caused by Russia’s military actions against Ukraine. A conclusion was made about the need to get acquainted with these processes, taking them into account for the development of the modern domestic educational space.